SISTEM INFORMASI AKUNTANSI (SIA) PENERIMAAN KAS PERUMDAM TIRTA DHARMA PURABAYA KABUPATEN MADIUN - Ardyan Firdausi Mustoffa; Aik Aviska; Yutt Puja Kusuma Lindayasa (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
An accounting information system is a process for collecting, processing, and storing financial-related data for making decisions. The reason of this study is to determine the monetary course of payment receipts from customers. To find out the finances of the customer by interviewing the finance department employee. The outcomes of this observe are in the form of a flowchart at the form of images that have meaning and writing.